Correlations between post-collisional Orosirian alkaline igneous suites from Bahia and Minas Gerais: fragments of an alkaline province? - Chaves, Alexandre de Oliveira (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2015)
Starting from age, there are many similarities between 1.90 Ga sodic Lagoa Real (Bahia) and 1.95 Ga potassic Gouveana (Minas Gerais) alkaline igneous suites. Both have lithotypes ranging from lamprophyres and monzonites to syenites and quartz-syenites, all of them belonging to the silica-saturated alkaline series. It is suggested that the partial melting of lithospheric mantle, which had been metasomatized by fluids from a subducted slab before the collision, would had generated a lamprophyric magma. The fractional crystallization of such magma would led to the appearance of monzonitic magmas, which in turn evolved to syenitic and quartz-syenitic ones. Both alkaline suites are inside N-S trending structural domain, with more than 1,000 km in length, in which occur several alkaline associations such as the 2.0 Ga syenitic suite at the southern edge of the São Francisco Craton (Minas Gerais), the Guanambi batolith (2.05 Ga, Bahia) and its lamprophyric, monzonitic, and syenitic terms, with genesis associated to the Paciência suite (Minas Gerais), and also the 2.0 Ga Angico dos Dias syenitic-carbonatitic-lamprophyric complex (Bahia). Apparently, all these associations represent the fragments of a 1,90 to 2,05 Ga Minas-Bahia Orosirian post-collisional alkaline province.
Keywords: Alkaline suite; Alkaline province; Orosirian; Post-collisional; São Francisco Craton